1993
DOI: 10.1071/mf9930687
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme variation in south-eastern Australian samples of the blue-eye or deepsea trevalla, Hyperoglyphe antarctica Carmichael 1818 (Teleostei: Stromateoidei)

Abstract: Six samples (n =67 to 154) of blue-eye or deepsea trevalla were collected from south-eastern Australia (seamounts off New South Wales, a seamount south-east of Tasmania called the Cascade Plateau, off the east, south and west coasts of Tasmania, and off the coast of South Australia). All fish were analysed by starch or cellulose acetate electrophoresis for the products of seven polymorphic loci (defined in this study as those with an average heterozygosity greater than 0.06); a minimum of 24 fish per area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Similar levels of gene flow, with little to no evidence of seamount population structure, have been observed between populations of fish (e.g. Martin et al 1992;Bolch et al 1993), corals (e.g. Smith et al 2004a;Thoma et al 2009), and squat lobsters and a planktotrophic gastropod (e.g.…”
Section: Patterns Of Genetic Connectivitymentioning
confidence: 59%
See 2 more Smart Citations
“…Similar levels of gene flow, with little to no evidence of seamount population structure, have been observed between populations of fish (e.g. Martin et al 1992;Bolch et al 1993), corals (e.g. Smith et al 2004a;Thoma et al 2009), and squat lobsters and a planktotrophic gastropod (e.g.…”
Section: Patterns Of Genetic Connectivitymentioning
confidence: 59%
“…For example, investigations of polymorphic allozymes in the fish Hyperoglyphe antarctica and three mitochondrial gene regions in the fish Pseudopentaceros wheeleri revealed a lack of differentiation between different populations inhabiting neighboring seamounts and adjacent non‐seamount areas (Martin et al. 1992; Bolch et al. 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell mass was sonicated on ice twice for 10 s. Cell extracts were used immediately for allozyme studies. Two electrophoretic systems were used as described by Bolch et al (1993). The following six enzymes were found to have poor activity or were not clearly resolved and were not examined further: amino peptidase (Leu-Gly-Gly substrate, PEP1), amino peptidase (Leu-Tyr substrate, PEP2), glycerol-3-phosphate dehydrogenase (G3PDH), fumarate hydratase (FH), isocitrate dehydrogenase (IDH), and malic enzyme (ME).…”
Section: Methodsmentioning
confidence: 99%
“…Tagging studies of individual yellowfin and bigeye tuna also found that they moved from seamount areas to non-seamount areas (Itano and Holland 2000;Sibert et al 2000). Genetic studies on fish have also found that there are no differences between different populations found on neighboring seamounts and adjacent non-seamount areas (Bolsch et al 1993;Borets 1979). Although these studies have shown a lack of isolation between studies, they primarily target large fishes that would be the most mobile of all seamount fauna.…”
Section: Seamount Population Connectivitymentioning
confidence: 99%